Under the Shadow of Uncertainty: A Longitudinal Study Tracing the Pathway From Future Uncertainty to Psychological Distress Through Social Media Addiction and Emotional Exhaustion - Jingwen Liang; Xiao Zhang; Dennis Ka Kuen Leung; Louis Leung (Social Media + Society)
Using two-wave panel survey data collected 12 months apart from a random sample of 447 Hong Kong respondents, this study builds upon the stress–strain–outcome model to examine the relationships among future uncertainty stress, social media addiction, emotional exhaustion, and psychological distress. The cross-lagged panel analysis revealed significant associations between future uncertainty stress, social media addiction, and psychological distress. Furthermore, social media addiction and emotional exhaustion were significant mediators between future uncertainty stress and psychological distress. These findings could enrich the understanding of how uncertainty stress contributes to psychological distress in an era characterized by pervasive digital connectivity.